Groundwater nitrate as a potential contributing source of acid and metalliferous drainage - Harck, T; Weber, P; Gemson, W (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Nitrate from ammonium nitrate fuel oil (ANFO) explosives used in mining/quarrying activities can be an environmental concern due to the solubility of nitrogenous contaminants and mobility over moderate timescales. In contrast, acid and metalliferous drainage (AMD), can be a long-term issue. A further concern especially relevant to closure planning is the combination of the two: elevated anthropogenic nitrate potentially leading to oxidation of pyrite in mining-affected geological units. Lithotrophic denitrification is the microbially-catalysed oxidation of sulphide to sulphate and conversion of nitrate to nitrogen gas through the transfer of electrons from sulphide to nitrate. This produces one quarter of the acidity compared to the oxidation of pyrite by oxygen and occurs under anoxic conditions in the absence of organic carbon. The process decreases groundwater nitrate concentrations, increases sulphate concentrations, and potentially increases ferrous iron. In experimental incubations of pure quartz-pyrite mixtures with/without microbial inoculations Reid et al. (2016) indicated daily acidity production rates of 0.013 to 0.117 kg H₂SO₄/t for starting nitrate concentrations of 180 mg/L and sulphide concentrations of 1.8 wt%. We present calculations of acidity production, groundwater flow, and alkalinity supply from two lithological units: the Brockman Iron Formation and the Mount McRae Shale (Pilbara Region, Western Australia). The former is a key host of iron ore mineralisation, while the latter is a key potential source of AMD. Groundwater in both units may potentially be impacted by anthropogenic nitrate leached from waste rock and pit walls on mine sites, including after closure. Using published pyrite concentrations, reaction stoichiometries, and nitrate concentrations, pyrite oxidation by nitrate could produce a total acidity of the order of 0.04 to 0.15 kg H₂SO₄ /t. Our calculations show low groundwater flow rates limit nitrate supply and significantly reduce the rate of acidity release if all pyrite is oxidised. We conclude pyrite oxidation by groundwater nitrate under anoxic conditions is not likely to lead to significant subsurface plumes of AMD impacted groundwater for the stratigraphical units assessed.
Keywords: nitrate